Charakter prawny rady społecznej w samodzielnym publicznym zakładzie opieki zdrowotnej - Michał Gornowicz (Studia Administracyjne)
The basis of the conducted research is a desire to determine the legal character of social councils in independent public health care institutions, which will consequently make it possible to formulate de lege ferenda postulates improving and strengthening the exercised control over the indicated medical institutions. De lege lata, the current manner of legal shaping of social councils makes it a facade, deprived of any authority enabling effective implementation of statutory objectives accompanying their establishment within the broadly understood social control of independent public healthcare institutions. The aim of this publication is to determine their position and the importance of social councils. As a research thesis, it was assumed that the competences granted to the social councils do not favour the realisation of the statutory objective of ensuring effective social supervision over the activities of independent public social care institutions. The research thesis formulated requires answers to several intermediate questions. One is to confirm the legal nature of the social councils assumed above. Another aim of the article is to indicate the scope of competence and the effectiveness of the influence of social councils on the activities of the director of an independent public health care institution. The realization of the indicated research objective will take place on the basis of the dogmatic-legal method consisting in the analysis of the previous doctrinal and judicial jurisprudence, which will consequently allow for the assessment of the scale of the usefulness of the social councils in the current activity of the health care entity. The research carried out leads to the conclusion that the shape of the current provisions regulating the functioning of social councils does not fulfil the original intention of the legislator - i.e. to ensure effective social supervision over the activities of independent public health care institutions. In view of the above, the repeal of the provisions on social councils should be submitted for consideration, with the simultaneous tightening of the provisions on the discipline of public finances in terms of the proper spending of funds in the operation of public health care institutions. An alternative to the presented solution to the problem may be a change in the provisions consisting in replacing social councils with control and supervisory bodies, e.g. audit commissions, which would comprise specialised members duly prepared for the powers exercised, and which would have a binding and not an opinion character. Thus, the control exercised over a particular healthcare entity would be of a real and not fictitious nature, while at the same time improving the decision-making process within the healthcare entity.